2020
DOI: 10.22271/chemi.2020.v8.i1g.8305
|View full text |Cite
|
Sign up to set email alerts
|

Personal, socio-economic, communication and psychological characteristics of dairy farmers

Abstract: Results showed that, the majority of the respondents belonged to middle aged (53.00 %), educated up to secondary school (50.00 %), (49.00%) had medium family, (78.50 %) belonged to nuclear type family, (33.00 %) possessed small land holding (up to 1.01 to 2.00 ha.), (76.50 %) possessed medium herd size, (79.00 %) possessed discript breeds, (63.00 %) had medium dairy farming experience, (68.50 %) had medium level annual income, (92.50 %) had medium level of sale of milk, (71.50 %) belonged to medium level of sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…A glance at Table : 1 was found that majority (39.70%) of the respondents sold 5 to 8 liters of milk per day followed by 35.45 per cent and 24.85 per cent of the respondents who sold less than 5 liters and more than 8 litres of milk respectively. Koli et al, (2020) revealed that majority of the respondents (92.50 %) had medium level of milk sale category…”
Section: Milk Salementioning
confidence: 96%
“…A glance at Table : 1 was found that majority (39.70%) of the respondents sold 5 to 8 liters of milk per day followed by 35.45 per cent and 24.85 per cent of the respondents who sold less than 5 liters and more than 8 litres of milk respectively. Koli et al, (2020) revealed that majority of the respondents (92.50 %) had medium level of milk sale category…”
Section: Milk Salementioning
confidence: 96%